GINGIVITIS, GUM INFLAMMATION– SYMPTOMS, ETIOLOGY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Gingivitis, gum inflammation (lat. gingivitis) is inflammation of the gums without breaking the integrity of the tooth-gum joints. If not treated in time, gingivitis can turn into periodontitis, a destructive form of periodontal disease. Gum inflammation is often manifested by swelling or bleeding gums.